(untitled) (Proceedings of International Educators Conference, 2023)
Artificial intelligence (AI) has emerged as the most widely applicable field across varied industries. Being an evolving technology, it may be quite useful in sensitive areas such as cyber security where there is a dire need for implementation of AI technologies, such as expert systems, neural networks, intelligent agents, and artificial immune systems. The primary reason for AI fitment to cyber security area is its ability to detect anomalies proactively and predictively in the network, thereby working towards securing the network before the damage related to loss of data and/or reputation is done. There are different types of AI technologies as mentioned above that could be applied in cyber security in its varied forms. In this paper, the emphasis is on specific AI technologies that can bring unique benefits to the cyber security field with its unique applicability to different scenarios. The outcome of this study shows that AI technologies such as expert systems, neural networks, intelligent agents, and artificial immune systems are transforming the landscape for managing cyber threats.